Search for CP violation using triple product asymmetries in [Lambda] 0b→pK− π + π −, [Lambda] 0b→pK−K+K− and [Xi] 0b→pK−K− π + decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2018)
A search for CP and P violation using triple-product asymmetries is performed with Λ b 0 → pK−π+π−, Λ b 0 → pK−K+K− and Ξ b 0 → pK−K−π+ decays. The data sample corresponds to integrated luminosities of 1.0 fb−1 and 2.0 fb−1, recorded with the LHCb detector at centre-of-mass energies of 7 TeV and 8 TeV, respectively. The CP - and P - violating asymmetries are measured both integrating over all phase space and in specific phase-space regions. No significant deviation from CP or P symmetry is found. The first observation of Λ b 0 → pK−χc0(1P)(→π+π−, K+K−) decay is also reported. Open image in new window